Cervical screening in Denmark – a success followed by stagnation. (4th March 2018) - Lynge, Elsebeth; Andersen, Berit; Christensen, Jette; Ejersbo, Dorthe; Jochumsen, Kirsten; Johansen, Tonje; Kristensen, Jette Kolding; Larsen, Lise Grupe; Mehnert, Frank; Mikkelsen, Ellen; Nielsen, Karsten; Rygaard, Carsten; et al.
Abstract: Introduction: Despite an intensive screening activity, the incidence of cervical cancer in Denmark has remained stable for the last 15 years, while regional differences have increased. To search for explanations, we investigated possible weaknesses in the screening program. Material and methods: Data on the screen-targeted women were retrieved from Statistics Denmark. Data on screening activity were retrieved from the annual reports from 2009 to 2015 on quality of cervical screening. Coverage was calculated as proportion of screen-targeted women with at least one cytology sample within recommended time intervals. Insufficient follow-up was calculated as proportion of abnormal and unsatisfactory samples not followed up within recommended time intervals. Diagnostic distribution was calculated for samples with a satisfactory cytology diagnosis. Results: Coverage remained stable at 75%–76% during the study period. Annually, approximately 100, 000 women are screened before they are eligible for invitation, and 600, 000 invitations and reminders are issued resulting in screening of 200, 000 women. In 2009, 21% of abnormal and unsatisfactory samples were not followed up within the recommended time interval; a proportion that had decreased to 15% in 2015. Overall, 11% of satisfactory samples with a cytology diagnosis were abnormal, but with surprising variation from 6% to 15% across regions. Discussion: The success of a screening program depends first of all on coverage and timely follow-up of abnormal findings. Our analysis indicated that the currently high incidence of cervical cancer in Denmark may partly be due to low screening coverage. Also worrisome is a high proportion of non-timely follow-up of abnormal findings. Innovative ways to improve coverage and follow-up are urgently needed.